5 × 5 25 Gbit/s WDM-MDM - Fazea, Yousef; Amphawan, Angela (Walter de Gruyter, 2015)
Wavelength-division multiplexed-passive optical network (WDM-PON) is a revolutionary high-capacity and scalable broadband access network. This paper capitalizes on Laguerre–Gaussian (LG) modes to reduce modal dispersion and increase data capacity.A data rate of 25 Gbit/s is attained for a multimode fiber link by multiplexing five LG modes on five wavelengths centered at 1,550.12 nm for a distance up to 800 m.